Ergonomics effects of work pace and work:rest ratio on repetitive powered handtool operations - Lin, J.-H; McGorry, R. W.; Maikala, R. V. (2012 IEEE International Conference on Industrial Engineering and Engineering Management, 2012)
Repetitive power tool use is associated with work-related upper extremity musculoskeletal disorders. Using a pneumatic nutrunner, 21 men completed twelve 360 repetitive fastener-driving sessions on three joints (hard, soft, and control) at slow and fast pace, and two different work:rest patterns. Handgrip force, hand motion, and localized blood volume at the forearm were collected throughout each session. For the control joint, the mean grip force exerted was 39.6% of maximum voluntary exertion (MVE) whereas during hard and soft joint sessions it was 48.9% MVE and 56.9% MVE, respectively. Further, a greater grip force decrease was resulted while operating soft and hard joints as compared to the control joint, suggesting considerable upper extremity muscular effort. Fast work pace resulted in higher average grip forces by participants but a greater decrease in the force as the session progressed. Providing rest breaks reduced perceived exertions. The findings provide knowledge for assembly task design to reduce the hand/arm injury risks.